SOLUTIONS FOR THE NEW TASKS IN AERODYNAMICS IN THE PROCESS OF CERTIFICATION OF AIRPLANCE OF TRASPORT CATEGORY – ANTI-ICE SYSTEM - V. I. Shevyakov (Научный вестник МГТУ ГА, 2017)
There are considered new tasks in aerodynamics in the process of certification of airplanes of transport category. The procedure for optimal location of ice detector at the transonic airplane and means of compliance with certification requirements for automatic engagement of anti-ice protection.